2012
DOI: 10.1117/1.jbo.17.5.055002
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a theoretical model to examine blood oxygenation dependent optoacoustics

Abstract: Abstract. A theoretical model investigating the dependence of optoacoustic (OA) signal on blood oxygen saturation (SO 2 ) is discussed. The derivations for the nonbandlimited and bandlimited OA signals from many red blood cells (RBCs) are presented. The OA field generated by many RBCs was obtained by summing the OA field emitted by each RBC approximated as a fluid sphere. A Monte Carlo technique was employed generating the spatial organizations of RBCs in two-dimensional. The RBCs were assumed to have the same… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…Experimental measurements have shown that the frequency location of these spectral minima shift depending on the RBC morphology, which can be used to differentiate healthy and unhealthy RBCs [31]. Other theoretical and experimental studies of RBCs show that UHF spectral features can be used to detect RBC morphological variations due to malaria infection [32], RBC oxygenation [33], and RBC aggregation [34] due to changes in the UHF spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental measurements have shown that the frequency location of these spectral minima shift depending on the RBC morphology, which can be used to differentiate healthy and unhealthy RBCs [31]. Other theoretical and experimental studies of RBCs show that UHF spectral features can be used to detect RBC morphological variations due to malaria infection [32], RBC oxygenation [33], and RBC aggregation [34] due to changes in the UHF spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…In the past five years, several groups have employed the use of PA radiofrequency analysis to differentiate prostate adenocarcinoma tumors from normal tissue [31], detect the presence of red blood cell aggregation [30], [32], identify various stages of liver disease [29], [33] and characterize bone and joint microstructure in osteoporosis [34] and rheumatoid arthritis [35]. Theoretical models have also been developed for understanding the spectral features that arise from tissue microstructural changes [36], [37], [38], [39], [40], [41], [42]. Combining functional aspects of PA imaging (based on optical spectroscopy) with structural information (based on RF frequency analysis) can potentially be used to better monitor cancer treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…(2) as a Gaussian function. 36 Equation (3) then becomes the expression for the band-limited (BL) PA pressure field for a collection of RBCs by multiplying its pressure by the Gaussian function representing the transducer frequency profile 29,37 …”
Section: Theoretical Modelmentioning
confidence: 99%